Internet connectivity disruption in Honduras (Honduras) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity disruption detected in Honduras. Data sourced from IODA.
Network Disruption Incident ID: HN-2026-0023. Severity: critical. Confidence: 70%